2018
DOI: 10.3233/cbm-171089
|View full text |Cite
|
Sign up to set email alerts
|

The potential predictive value of circulating immune cell ratio and tumor marker in atezolizumab treated advanced non-small cell lung cancer patients

Abstract: The circulating immune cell ratios and plasma tumor marker levels were related with clinical efficacy of atezolizumab therapy. These factors could be potential predictive marker for anti-PD-L1 therapy in advanced non-small cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 44 publications
2
23
1
1
Order By: Relevance
“…In advanced NSCLC patients treated with Atezolizumab, disease control was associated with decreased frequencies of Tregs and Lin − HLA-DR − CD33 + CD11b + MDSCs and a reduction in NLR after treatment (101).…”
Section: Circulating Biomarkersmentioning
confidence: 96%
“…In advanced NSCLC patients treated with Atezolizumab, disease control was associated with decreased frequencies of Tregs and Lin − HLA-DR − CD33 + CD11b + MDSCs and a reduction in NLR after treatment (101).…”
Section: Circulating Biomarkersmentioning
confidence: 96%
“…Another trial [139] showed a relationship between clinical efficacy of atezolizumab therapy and lymphocyte ratio modifications, but no baseline value was correlated with the outcomes.…”
Section: Lymphocyte Ratiomentioning
confidence: 99%
“…In recent years, new imaging examinations, such as PET and functional magnetic resonance imaging (MRI) have been shown to have advantages in pseudoprogression diagnosis by detecting the metabolism or specific macrophages in tumors. The value of biomarkers has also been emphasized, and Zhou’s study in non-small-cell lung cancer (NSCLC) showed that if CA125, CA199, or CEA increase by less than 50% above baseline after immunotherapy, it could still indicate the disease control ( 8 ). This is in agreement with the biomarker variation in our case.…”
Section: Discussionmentioning
confidence: 99%